International perspective on the new 2019 ATS/IDSA CAP guideline – a critical appraisal by a global expert panel (2020)
In 2019, the American Thoracic Society (ATS) / Infectious Diseases Society of America (IDSA) issued a substantial revision of the 2007 guideline on community-acquired pneumonia (CAP). Despite generalization of infectious disease guidelines is limited due substantial geographic differences in microbiological etiology and antimicrobial resistance, the ATS/IDSA guidelines are frequently applied outside the USA. Therefore, this project aimed to give a perspective on the ATS/IDSA CAP recommendations related to the management of CAP outside of the USA. For this, an expert panel comprised of 14 international key opinion leaders in the field of CAP from 10 countries across 5 continents, who were not involved in the 2019 guideline, was asked to subjectively name the five most useful, the most critical and the recommendation that can not be applied to their respective region. There was no formal consensus process and the paper reflects different opinions. Recommendations welcomed by the vast majority of the international pneumonia experts included the abandonment of the concept of “health-care associated pneumonia” (HCAP), the more restrictive indication for empiric macrolide treatment in outpatients, the increased emphasis on microbiological diagnostics, and addressing the use of corticosteroids. Main criticisms included the somewhat arbitrary choice of a 25% resistance threshold for outpatient macrolide monotherapy. Experts from areas with elevated mycobacterial prevalence particularly opposed the recommendation of fluoroquinolones, even as an alternative.